International clinimetric evaluation of the MG‐QOL15, resulting in slight revision and subsequent validation of the MG‐QOL15r. Issue 6 (7th November 2016) - Burns, Ted M.; Sadjadi, Reza; Utsugisawa, Kimiaki; Gwathmey, Kelly G.; Joshi, Amruta; Jones, Sarah; Bril, Vera; Barnett, Carolina; Guptill, Jeffrey T.; Sanders, Donald B.; Hobson‐Webb, Lisa; Juel, Vern C.; et al.
ABSTRACT: Introduction : The MG‐QOL15 is a validated, health‐related quality of life (HRQOL) measure for myasthenia gravis (MG). Widespread use of the scale gave us the opportunity to further analyze its clinimetric properties. Methods : We first performed Rasch analysis on >1, 300 15‐item Myasthenia Gravis Quality of Life scale (MG‐QOL15) completed surveys. Results were discussed during a conference call with specialists and biostatisticians. We decided to revise 3 items and prospectively evaluate the revised scale (MG‐QOL15r) using either 3, 4, or 5 responses. Rasch analysis was then performed on >1, 300 MG‐QOL15r scales. Results : The MGQOL15r performed slightly better than the MG‐QOL15. The 3‐response option MG‐QOL15r demonstrated better clinimetric properties than the 4‐ or 5‐option scales. Relative distributions of item and person location estimates showed good coverage of disease severity. Conclusions : The MG‐QOL15r is now the preferred HRQOL instrument for MG because of improved clinimetrics and ease of use. This revision does not negate previous studies or interpretations of results using the MG‐QOL15. Muscle Nerve 54 : 1015–1022, 2016